Choke Box : a Fem-Noir - Milletti, Christina (Book collections on Project MUSE., 2019)
"When Edward Tamlin disappears while writing his memoir, Jane Tamlin (his wife and the mother of his young children) begins to write a secret, corrective 'counter-memoir' of her own. Calling the book Choke Box, she shares her insights into motherhood, reveals intimate, often irreverent, details about her family and marriage, and rejects--and occasionally celebrates--her suspected role in her husband's disappearance. Choke Box isn't Jane's first book. From her room in the Buffalo Psychiatric Institute, she slowly reveals a hidden history of the ghost authorship that has sabotaged her family and driven her to madness. Her latest work, finally written under her own name, is designed to reclaim her dark and troubled story. Yet even as Jane portrays her life as a wife, mother, and slighted artist with sardonic candor, her every word is underscored by one belief above all others: the complete truth is always a secret. Words cannot set us free. But the stories we tell may help us survive--if they don't kill us first"--